Edukasi Ibu Hamil Dengan Pengetahuan Perilaku Perawatan Payudara di Praktek Mandiri Bidan Dewi Ciselia - Ciselia, Dewi; Ariyani, Yulinda (Nanggroe: Jurnal Pengabdian Cendikia, 2025)
The low knowledge of pregnant women about the importance of breast care during pregnancy will affect breast milk production and the behavior of exclusive breastfeeding in babies from birth to six months of age. One factor that influences the success of breast care is the knowledge of pregnant women. Problems that can arise in pregnant women who do not do breast care during pregnancy include nipple pain, breast engorgement, mastitis, breast abscesses, and breast milk flow problems. The purpose of this activity is to provide education for pregnant women with knowledge of breast care behavior. The method of implementing this Community Service Program is community education in the form of health counseling, evaluated by pre-test and post-test. The method of implementing the service is to provide education to pregnant women through discussions using ebooklet media about the importance of breast care behavior. The number of participants who attended was 50 people, 2 students, and 5 midwives. The activity started from the planning, implementation, evaluation, to the preparation of reports. The results of the activity showed changes in knowledge with an average of 58.3% of participants' knowledge being in the poor category and 58.3% of the results being in the good category. In terms of skills, all participants (100%) were able to understand the importance of breast care behavior. Conclusion: Educational activities on the importance of breast care behavior can be an effort to increase knowledge and promote health.